2016
DOI: 10.1175/ei-d-15-0032.1
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing the Agronomic Yield Gaps of Maize by Improved Soil, Cultivar, and Agricultural Management Practices in Different Climate Zones of Northeast China

Abstract: Northeast China (NEC) is one of the major agricultural production areas in China, producing about 30% of China's total maize output. In the past five decades, maize yields in NEC increased rapidly. However, farmer yields still have potential to be increased. Therefore, it is important to quantify the impacts of agronomic factors, including soil physical properties, cultivar selections, and management practices on yield gaps of maize under the changing climate in NEC in order to provide reliable recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
(29 reference statements)
0
15
0
1
Order By: Relevance
“…Crop simulation methods can be used to estimate crop growth, yield, and improve agricultural management systems by allowing farmers to be prepared for climatic conditions of the forthcoming season [9,[72][73][74][75]. Crop modelling and remote sensing are two methods that enable government agencies, private industry, and researchers to estimate yield before harvest.…”
Section: Complex Models Used In Yield Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Crop simulation methods can be used to estimate crop growth, yield, and improve agricultural management systems by allowing farmers to be prepared for climatic conditions of the forthcoming season [9,[72][73][74][75]. Crop modelling and remote sensing are two methods that enable government agencies, private industry, and researchers to estimate yield before harvest.…”
Section: Complex Models Used In Yield Estimationmentioning
confidence: 99%
“…Potential yield refers to the maximum yield that can be attained by a crop in a given environment [4]. Potential yield is largely determined by a specific combination of factors, such as solar radiation, soil type, temperature, plant density, genetic potential of a given genotype, biotic and abiotic constraints [8][9][10]. However, realized yield, also known as attainable yield, obtained by a farmer is more frequently influenced by poor agricultural practices [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjusted R 2 of the constructed model was 51.6% which is not a high value. The yield of crops in field conditions is mainly affected by soil and climatic factors; however, for the artificially cultivated forage crops, management methods such as cultivar selection, timing of fertilization, amount of fertilizing, weed and pests management become the strategic factors affecting the variance of the crop yield (Liu et al, ). Limited to the insufficient current data recording condition, the relevant data set was not prepared in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that different regions expose the crop to different types of environmental stress and the effect caused by changing input parameters depends on the types of stresses present in the environment. However, overall the soil properties, cultivar selection, and management practices are very important to yield; a study [46] with APSIM-maize in Northeast China found that yields can be increased by 9% by improving soil physical properties, by 23% by changing cultivars, and by 34% by improving management practices.…”
Section: Methodsmentioning
confidence: 99%